Analysis of Semarang Container Terminal Dock Operation Productivity Through Automatic Rubber Tyred Gantry (ARTG) Performance - Aramita, Ankaa Neha; Rahayu, Trisnowati; Pribadi, Teguh; Sianturi, Intan (Universitas Hang Tuah, 2026)
This study aims to analyze the productivity of Semarang Container Terminal dock operations through the performance of automatic rubber tyred gantry (ARTG). The research approach used is descriptive quantitative with data collection methods through direct observation, interviews, and documentation. A total of seven samples were obtained from the documentation in the form of ARTG performance reports and dock operation productivity. Data were analyzed using descriptive statistics and trend tables to determine the performance of ARTG and the productivity of container terminal dock operations. In addition, using the Spearman-rho Rank Correlation Test (ρ) to determine the relationship between ARTG performance and container terminal dock operation productivity based on the company's monthly data. The results of the study showed fluctuations in ARTG performance and dock operation productivity with an average ARTG performance through the availability indicator of 98.21% and an average value of dock operation productivity through the Box Ship per Hour (BSH) indicator of 43.34 bph, as well as a significant and very strong relationship between ARTG performance and dock operation productivity with a significance value of 0.012 < (0.05) with a correlation coefficient value of 0.865. In addition, the results of observations and interviews also show a relationship between ARTG performance and the productivity of container terminal dock operations, as well as other supporting report data which are factors in the relationship between ARTG performance and dock operation productivity.